Management of tinea capitis in Israel: A comparative study. Issue 4 (17th May 2021) - Shemer, Avner; Gupta, Aditya K.; Galili, Eran; Daniel, Ralph; Kassem, Riad; Farhi, Renata; Grunwald, Hadas; Bamimore, Mary A.
Abstract: Background: Tinea capitis is a common fungal infection in Israel, most commonly caused by the dermatophyte Trichophyton tonsurans . Objectives: To investigate the effectiveness of oral antifungal monotherapy in producing clinical or complete cure. We also evaluated the impact of topical therapy (bifonazole 1% shampoo and/or betamethasone valerate 0.1% solution), prior to oral treatment, on patients' likelihood of clinical or complete cure. Methods: A retrospective chart review was conducted. Patients with mycologically confirmed tinea capitis were treated with one of four regimens: (1) terbinafine (greater than 40 kg: 250 mg/day, 20 to 40 kg: 125 mg/day, less than 20 kg: 62.5 mg/day), (2) itraconazole 5 mg/kg daily, (3) fluconazole 6 mg/kg daily, or (4) griseofulvin 20 mg/kg daily. We used generalized linear models (GLM) to determine whether there was a significant association between the odds of cure and choice of treatment. Results: The causative species was Trichophyton tonsurans in all but 6 cases that grew T violaceum . For pediatric patients, the odds of having complete or clinical cure within 6 weeks was greater if they used terbinafine compared to itraconazole, fluconazole, or griseofulvin (odds ratio [OR] = 9.06, P  = .047). The likelihood of complete or clinical cure within 8 weeks of oral therapy was lower if topical steroids were previously used compared to if topical antifungals were used prior to systemic treatment (OR = 0.29, P  = .046). Conclusions: Our findings substantiate prior literature demonstrating that terbinafine is non‐inferior to griseofulvin, itraconazole, and fluconazole in the therapy of pediatric tinea capitis caused by T tonsurans .